Relations entre capacités cognitives et communicatives d’enfants à retard mental: Relationship between the cognitive and communicative abilities in children with mental retardation - Nader-Grosbois, Nathalie (Revue francophone de la déficience intellectuelle, 2001)
Cette étude transversale a investigué les hypothèses de retard et de différence des modalités de développement des enfants à retard mental par rapport aux enfants tout-venant, durant la période sensori-motrice. Trente-cinq (35) enfants tout-venant et 35 enfants à retard mental ont été examinés au moyen des «Échelles d’Évaluation du Développement Cognitif Précoce» (Nader-Grosbois,1993), version revisée des «Infant Psychological Development Scales» (Uzgiris et Hunt, 1975), et des «Early Social Communication Scales» (Seibert et Hogan, 1982). Leurs performances ont permis d’explorer les relations globales et spécifiques entre capacités cognitives et capacités communicatives ainsi que d’appréhender la synchronie vs l’hétérochronie du rythme de développement de ces capacités. Dans les deux groupes, les relations globales entre capacités sont similaires; mais les relations spécifiques et l’hétérochronie développementale varient suivant l’âge et le stade cognitif modal des enfants. Chez les enfants à retard mental, sont relevées des stratégies cognitives et communicatives spécifiques. Abstract This cross-sectional study has explored the «delay» and «difference» hypotheses about modalities of psychological development in mentally retarded vs. normally developing children, for what regards the sensori-motor developmental period. Thirty-five (35) normally developing and 35 mentally retarded young children have been examined by means of the «Early Cognitive Development Evaluation Scales» (Nader-Grosbois, 1993) (a revised version of the «Infant Psychological Development Scales», Uzgiris & Hunt, 1975) and the «Early Social Communication Scales» (Seibert & Hogan, 1982). Performances displayed allowed to explore global and specific relationships between cognitive and communicative competencies as well as the developmental synchrony vs. heterochrony of these competencies. In both groups, global relationships between competencies are similar, but specific relationships as well as developmental heterochrony vary according to the age and cognitive modal stages considered. However, in the case of mentally delayed children, specific communicative and cognitive strategies have been observed.